COVID-Vaccination and Performance in Five Global Stock Market Indexes: Array - Ngwakwe, Collins (Acta Universitatis Danubius. Œconomica, 2021)
This paper analyses the response of stock markets to vaccine availability. Objective: the objective of this paper is to examine the differential effect of information about the arrival of COVID vaccine on the stock price performance of five main global stock market indexes. Prior work: the paper relies on the prior theory of Efficient Market Hypotheses (EMH). Method: data on stock price performance seven months before vaccine arrival and seven months within the vaccination period were from Trading Economics stock indexes archives for five main market indexes namely (Dow Jones, Shanghai, S&P, FTSE, and EURONEXT). The data were analysed using the t-test of mean difference in stock prices before and during vaccine at 5% alpha level. Findings: results for the five indexes analysis show that stock prices during the arrival of vaccine significantly outweigh the stock prices before vaccine arrival at p-values below 0.01, which are lower than the alpha value of 5%. The mean stock price increases during vaccine arrival ranges from 7% to over 20% for the different indexes. Implications: The paper provides practical information for investors who need to know how sensitive the various indexes are to vaccine information. The paper also provides an avenue for future research to expand on this initial research on vaccine effect on stock prices. Furthermore, the paper presents a veritable case study for economics and finance postgraduate students in the universities. Value: This paper fills existing gap in knowledge by being the first to analyse the effect of COVID vaccine arrival on the stock price of five main global stock indexes and contributes by indicating that stock indexes are sensitive to vaccine production with diverse percentages of sensitivity.